2021
DOI: 10.1080/13683500.2021.1974358
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review on the use of big data for sustainable tourism

Abstract: Sustainable tourism research focuses on mitigating or remediating environmental, social and economic impacts on tourism. In the past years, Big Data approaches have been applied to the field of tourism allowing for remarkable progress. However, there seems to be little evidence to support that such approaches are an inspiration to sustainable tourism and are being implemented. In this context, we aim to obtain a comprehensive overview of the use of Big Data in sustainable tourism to address various issues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 91 publications
0
10
0
1
Order By: Relevance
“…Through keyword co-occurrence maps based on previous studies by Moosavi et al (2021) and Van Eck and Waltman (2018), we concluded that the most used keywords over the last 5 years were Tourism product, data, sustainability, and technology. This means that the classical activity of sustainable tourism has become obsolete (Leo´n-Go´mez et al, 2021) and is evolving into other tourism activities where sustainability and technology are robust cooperation tools (Rahmadian et al, 2022;Santos-Jae´n et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Through keyword co-occurrence maps based on previous studies by Moosavi et al (2021) and Van Eck and Waltman (2018), we concluded that the most used keywords over the last 5 years were Tourism product, data, sustainability, and technology. This means that the classical activity of sustainable tourism has become obsolete (Leo´n-Go´mez et al, 2021) and is evolving into other tourism activities where sustainability and technology are robust cooperation tools (Rahmadian et al, 2022;Santos-Jae´n et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…interpersonal and organizational level) by conducting multilevel analysis. A recent systematic review article indicated that ‘big data’ can be utilized to understand intrinsic factors that affect tourists’ behaviors, because tourists tend to leave their digital footprint on social media or other online platforms (Rahmadian et al , 2021). Findings from big data analysis can also enable practitioners and policymakers to promote sustainable tourism.…”
Section: Discussionmentioning
confidence: 99%
“…In the hospitality and tourism setting, the adoption of this framework has been experiencing significant growth, and recent systematic reviews have, therefore, been applying this methodology (i.e. Lopes and Penela, 2021; Oláh et al , 2020; Kim and So, 2022; Rahmadian et al , 2022).…”
Section: Methodsmentioning
confidence: 99%